THEORETICAL AND METHODOLOGICAL ASPECTS OF THE DEVELOPMENT METHODS OF RUSSIAN UNIVERSITIES' SCIENTIFIC RESEARCH PERFORMANCE INTEGRATION INTO THE NATIONAL INNOVATION SYSTEM - E. Belova (Вестник университета)
Theoretical and methodological approaches to the development methods of higher educational institutions' integration into national innovative system of the Russian Federation are elaborating. Although the tasks and the purpose of the scientific research performance of the universities' integration into Russian economy are systematized. On the basis of foreign practice, there are constructive ways to optimize the methods of research work results into the manufacture to improve foreign trade competitiveness of Russia.